Investigating a new alarming outbreak of flavescence dorée in Tuscany (Central Italy): molecular characterization and map gene typing elucidate the complex phytoplasma ecology in the vineyard agroecosystem - Pedrelli, Athos; Carli, Marco; Panattoni, Alessandra; Pellegrini, Elisa; Rizzo, Domenico; Nali, Cristina; Cotrozzi, Lorenzo (Frontiers in Plant Science, 2024)
Flavescence dorée (FD) is a major grapevine disease in Europe, despite the quarantine status of its causal agent [FD phytoplasma (FDp)] and the mandatory monitoring and vector control practices. As alarming FD epidemic outbreaks continue to appear in Tuscany (Central Italy), a 4-year survey was carried out in the main wine-growing areas of the region, where FD presence was investigated in both primary and secondary FDp hosts and vectors, i.e., Vitis vinifera (VV), Clematis vitalba (CV), Alnus glutinosa (AG), Scaphoideus titanus (ST), and Dictyophara europaea (DE). This work i) confirmed FD diffusion in almost the whole of Tuscany and even with an increased occurrence rate (approximately 50% of the samples tested positive); ii) highlighted a complex FDp ecology also in the Tuscan vineyard agroecosystem, as FDp was reported not only in VV and ST but also in secondary vectors (DE) and hosts (AG and CV); iii) reported nine FDp strains (three of which were novel) belonging to all the three methionine aminopeptidase (map) clusters, i.e., map-FD1, map-FD2, and map-FD3, with the map-FD3/M51 genotype mostly reported in not only VV but also DE and CV; and iv) further confirmed a complex FDp ecology in the vineyard agroecosystem, also by phylogenetic analyses carried out at both Italian and European levels, which also showed some relations between the Tuscan FDp strains and those reported in the Balkan and the French scenarios. We believe that the outcomes reported here will be useful in preventing and controlling the spread of harmful FD.